Battle for the elephants - Douglas-Hamilton, Iain.; Jackman, Brian; Douglas-Hamilton, Oria. (New York : Viking, 1992)
Tells the inside story of how the Douglas Hamilton's lead the fight to conserve the African Elephant and end the international ivory trade.
Includes bibliographical references (p. [356]-359) and index.
Booklist.
Library Journal Starred.
Publisher's Weekly.
Adult.
Adult
Keywords: African elephant; Wildlife conservation -- Africa; African elephant; Wildlife conservation -- Africa